Estimasi Curah Hujan Kota Banjarbaru Kalimantan Selatan Menggunakan Metode Jaringan Syaraf Tiruan - Rizalihadi, Muhammad; Siregar, Simon S; Sudarningsih, Sudarningsih (Lambung Mangkurat University Press, 2009)
Rain is weather phenomenon caused by climateâs physical conditionsof atmosphere variables such as temperature, air pressure, air density, humidityand wind of velocity. Many researches on rain have been undertaken inIndonesia. Many statistic models are resulted from those researches;nevertheless, in statistic models climateâs physical conditions are not consideredas components which affect the rain occurrence. Besides, estimating the amountof rain that is to fall-whether it is increasing, decreasing, or static- with statisticmodels is still unsure. Physical and mathematical approaches of weathervariables only are not enough to estimate rainfall. More interpretations areneeded to apply. Therefore, this research implements a way to estimate dailyrainfall using a method called Artificial Neural Network. As parameter of theinputs of JST program, then the data of daily temperature, air humidity and windspeed play important roles, while the output which is manifested in daily rainfalltested in data scale, a period of 5-9 years. The results obtained show that JSTmethod enables us to estimate daily rainfall of Kota Banjarbaru.